EXPLORING YOUTH SOCIAL MEDIA USE FOR ENHANCEMENT OF AGRICULTURAL EXTENSION SERVICES IN RURAL AREAS OF NIGERIA: A SYSTEMATIC REVIEW - Nwabuaku Kanu, Winifred (African Journal of Social and Behavioural Sciences, 2024)
This study investigates the role of social media in enhancing agricultural extension services among youths in rural Nigeria, with a focus on its usage, the challenges encountered, and strategies for improvement. A systematic literature review was conducted using Google Scholar as the primary database to identify relevant studies. The search strategy employed Boolean operators to combine keywords such as “„youth,‟ „social media,‟ „agricultural extension services,‟ and „Nigeria‟ or „rural areas.‟” The inclusion criteria were tailored to select studies focusing on youth in rural areas of Nigeria, the use of social media platforms for agricultural extension, and studies that specifically address the Nigerian context. A total of 66 articles were initially identified 7 of which met the inclusion criteria after thorough screening and quality assessment. The results reveal that while platforms such as WhatsApp and Facebook are utilized by youths for agricultural information exchange, significant barriers, including limited ICT infrastructure, inadequate training, and sociocultural constraints, among others, impede their effectiveness. The study suggests that addressing these challenges through targeted policy interventions and capacity-building initiatives can increase the potential of social media as a tool for agricultural development. These insights can inform stakeholders on the benefits of leveraging social media to promote innovation, improve productivity, and support food security in rural Nigeria.